Serine-727 phosphorylation activates hypothalamic STAT-3 independently from tyrosine-705 phosphorylation - Breit, Andreas; Besik, Valeria; Solinski, Hans Jürgen; Muehlich, Susanne; Glas, Evi; Yarwood, Stephen J.; Gudermann, Thomas (Molecular Endocrinology, 2015)
Transcriptional activity of signal transducer and activator of transcription-3 (STAT-3) is a key element in the central regulation of appetite and energy homeostasis. Activation of hypothalamic STAT-3 has been attributed to cytokine-promoted phosphorylation at tyrosine-705 (Tyr-705). In nonhypothalamic cells, STAT-3 is also phosphorylated at serine-727 (Ser-727), but the functional significance of Ser-727 in the regulation of hypothalamic STAT-3 is not known. We used 2 hypo-thalamic cell lines and analyzed the effects of various hormones on STAT-3-dependent reporter gene activity and observed that IFN-7, epidermal growth factor (EGF), and bradykinin (BK) induce similar STAT-3 reporter activation. EGF and BK solely increased Ser-727 and IFN-7 increased Tyr-705 phosphorylation of STAT-3. Specific inhibition of ERK-1/2 activity blocked EGF-and BK-induced STAT-3 activation and Ser-727 phosphorylation. BK-induced ERK-1/2 activation occurred via EGF receptor transactivation. Consequently, the BK-mediated effects on STAT-3 were blocked by a specific EGF receptor antagonist. Next, we analyzed the effects of IFN-7 and EGF on the expression of the STAT-3-dependent genes thyroliberin-releasing hormone and suppressors of cytokine signaling-3. EGF but not IFN-7 enhanced thyroliberin-releasing hormone expression via STAT-3. With regard to suppressors of cytokine signaling-3, we observed prolonged expression induced by IFN-7 and a transient effect of EGF that required coactivation of the activator protein-1. Thus, EGF-promoted Ser-727 phosphorylation by ERK-1/2 is not only sufficient to fully activate hypo-thalamic STAT-3, but, in terms of targeted genes and required cofactors, entails distinct modes of STAT-3 actions compared with IFN-7-induced Tyr-705 phosphorylation.
CRIS-Team Scopus Importer:2024-07-10